Investigation of the size–property relationship in CuInS2 quantum dots. Issue 43 (15th October 2015) - Akdas, T.; Walter, J.; Segets, D.; Distaso, M.; Winter, B.; Birajdar, B.; Spiecker, E.; Peukert, W.
Abstract : Determination of the size–property functions via size-selective precipitation (SSP), analytical ultracentrifugation, absorption spectroscopy and transmission electron microscopy. Abstract : In this work we investigated fundamental properties of CuInS2 quantum dots in dependence of the particle size distribution (PSD). Size-selective precipitation (SSP) with acetone as poor solvent was performed as an adequate post-processing step. Our results provide deep insight into the correlation between particle size and various optical characteristics as bandgap energy, absorption and emission features and the broadness of the emission signal. These structure–property relationships are only achieved due to the unique combination of different analytical techniques. Our study reveals that the removal of 10 wt% of smallest particles from the feed results in an enhancement of the emission signal. This improvement is ascribed to a decreased quenching of the emission in larger particles. Our results reveal the impact of PSDs on the properties and the performance of an ensemble of multicomponent QDs and anticipate the high potential of controlling PSDs by well-developed post-processing.